Interaction of caveolin-1 with Ku70 inhibits Bax-mediated apoptosis. - Huafei Zou; Daniela Volonte; Ferruccio Galbiati (PLoS ONE, 2012)
Caveolin-1, the structural protein component of caveolae, acts as a scaffolding protein that functionally regulates signaling molecules. We show that knockdown of caveolin-1 protein expression enhances chemotherapeutic drug-induced apoptosis and inhibits long-term survival of colon cancer cells. In vitro studies demonstrate that caveolin-1 is a novel Ku70-binding protein, as shown by the binding of the scaffolding domain of caveolin-1 (amino acids 82-101) to the caveolin-binding domain (CBD) of Ku70 (amino acids 471-478). Cell culture data show that caveolin-1 binds Ku70 after treatment with chemotherapeutic drugs. Mechanistically, we found that binding of caveolin-1 to Ku70 inhibits the chemotherapeutic drug-induced release of Bax from Ku70, activation of Bax, translocation of Bax to mitochondria and apoptosis. Potentiation of apoptosis by knockdown of caveolin-1 protein expression is greatly reduced in the absence of Bax expression. Finally, we found that overexpression of wild type Ku70, but not a mutant form of Ku70 that cannot bind to caveolin-1 (Ku70 Φ→A), limits the chemotherapeutic drug-induced Ku70/Bax dissociation and apoptosis. Thus, caveolin-1 acts as an anti-apoptotic protein in colon cancer cells by binding to Ku70 and inhibiting Bax-dependent cell death.